The synthesis, characterization and spectral studies of Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) complexes with N,N-bis(2-{[(2-methyl-2-phenyl-1,3-dioxolan-4-yl) methyl]amino}butyl) N?,N?-dihydroxyethanediimidamide - Canpolat, E; Kaya, M (Taylor & Francis Ltd, 2005)
Co-II. Ni-II, Cu-II. Zu(II) and Cd-II complexes of N,N-bis(2-{[(2-methyl-2-phenyl-1,3-dioxolan-4-yl)methyl ]amino;butyl)N',N'-dihydroxyethanediimidamide (LH2) were synthesized and charaterized by elemental analyses, IR, H-1- and C-13-NMR spectra electronic spectra, magnetic susceptibility measurements, conductivity measurements and thermogravimetric analyses (TGA). The Co-II, Ni-II and Cu-II complexes of LH2 were synthesized with 1:2 metal ligand stoichiometry. Zn-II and Cd-II complexes with LH2 have a metal ligand ratio of 1 : 1. The reaction of LH2 with Co-II, Ni-II, Cu-II, Zn-II and Cd-II chloride give complexes Ni(LH)(2), Cu(LH)(2), Zn(LH2)(Cl)(2), Cd(LH2)(Cl)(2), respectively.
Keywords: synthesis of dioxime complexes; cobalt(II); nickel(II); copper(II); zinc(II) and cadmium(II)